One hundred names - Ahern, Cecelia 1981- (Harper, 2013)
Internationally bestselling author Cecelia Ahern's <One Hundred Names</ is the story of secrets, second chances, and the hidden connections that unite our lives'a universal tale that will grip you with its emotional power and mesmerize you with its magic.</ Scandal has derailed Journalist Kitty Logan's career, a setback that is soon compounded by an even more devastating loss. Constance, the woman who taught Kitty everything she knew, is dying. At her mentor's bedside, Kitty asks her'what is the one story she always wanted to write'</ The answer lies in a single sheet of paper buried in Constance's office'a list of 100 names'with no notes or explanation. But before Kitty can talk to her friend, it is too late.</ Determined to unlock the mystery and rebuild her own shaky confidence, Kitty throws herself into the investigation, using her skills and savvy to track down each of the names on the list and uncover their connection. Meeting these ordinary people and learning their stories, Kitty begins to piece together an unexpected portrait of Constance's life. . . and starts to understand her own.